Highly sensitive metamaterial biosensor operating in the terahertz regime - Naeem, Nadeem (2016)
Four metamaterial structures are presented in this thesis, which are designed to operate in terahertz frequency regime. The main objective of this study is to design terahertz metamaterial sensors that can be used as highly sensitive biosensors. Since every substance or material has its dielectric characteristics; these biosensors are designed to sense small changes appeared at the minute amount of samples called analytes when they are poured on the surface of the metamaterial structures. There is a change in transmission appeared at metamaterial structures which is due to the change in surface electric field localized in split gap areas. The first two planar metamaterial Spiral ring resonators were designed operating in terahertz frequency band. These subwavelength structures were categorized as Type-I and Type-II (two-turn and three-turn Spiral resonators). They are designed for use as sensitive metamaterial terahertz sensors. The unloaded fundamental frequency of was observed around 3.69 THz and 3.93 THz respectively. The two-turn and three-turn Spiral resonators based biosensors exhibit very high values of unloaded Q factor of 159 and 689. The other two terahertz sensors composed of split ring resoantors are also demonstrated as negative index metamaterials operating in terahertz regime. The Square and Hexagon spilt resonators are introduced as terahertz biosensors. The unloaded Q factor calculated for the Hexagon and Square split ring biosensors were observed at the operating frequencies of 3.2 THz and 3.31 THz are 33.64 and 42.1 respectively. There is significant shift in the transmission coeeficients were observed under loading conditions when the dielectric material as a biological sample of varrying permittivity and different material thickness were deposited on the surface of proposed biosensors. Such biosensors can be used in label free sensing of minute biological substances like protein, bacteria without harming their characteristics and the valuable indformation present in the cells due to the non ionizing characterisitcs of terahertz frequency.